CONTENT AND FORMS OF ACTIVITY OF THE INSTITUTION OF THE PRESIDENCY IN ACHIEVING EUROPEAN INTEGRATION SUCCESSES - Shkuro, Anton (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2024)
The article examines the processes that have reinforced Ukraine’s European integration trajectory, highlighting the pivotal role of the institution of the presidency as a central decision-making authorityfollowing the onset of Russia’s open military aggression against Ukraine in 2022. The author concludes that the Ukrainian response to the unjustified military actions of the Russian Federation did not result in panic and fear. Instead, it unified the nation in its efforts to strengthen and develop its state and political institutions that are tasked with making effective political decisions and providing the necessary conditions for the Ukrainian institution of presidency, particularly in matters of foreign policy. The article examines the issue of Ukraine’s European and Euro-Atlantic integration;solution to whichwas significantly bolstered by the full-scale invasion of the Russian armed forces in 2022. These events generated a mobilization potential within Ukrainian society concerning foreign policy priorities. It is emphasized that Ukraine’s top political leadership promptly applied for EU membership shortly after the introduction of martial law. In June 2022, the European Commission published its conclusions, leading to all EU member states granting Ukraine the status of a candidate for EU membership. The article analyzes the works of Ukrainian scholars who have studied the evolution of Ukraine’s European integration trajectory and the role of the institution of the presidency in this process. Special attention is given to the advancement of Ukraine’s Euro-Atlantic aspirations. The author positively notes that at the NATO Summit in Vilnius in 2023, the member states of the Alliance reaffirmed their commitment to Ukraine’s future accession to NATO. The article concludes that the communicative and political activities of the institution of the presidency have demonstrated to the international community the ability to make constructive proposals and secure positive decisions benefiting both Ukraine and its partners.